Differential performance of contrasting defensive traits of cocoons of two moth species against bird predation. Issue 3 (2nd July 2021) - Furukawa, Mariko; Nakanishi, Kosuke; Honma, Atsushi; Takakura, Koh‐Ichi; Matsuyama, Kazuyo; Hidaka, Naoya; Sawada, Hiroichi; Nishida, Takayoshi
Abstract: Prey defensive traits against predators can be categorized into primary defense (avoiding detection) and secondary defense (avoiding attack after detection). There are trade‐offs between these two defensive traits, which consider the cost of defense. To quantify the predation avoidance efficacy of both defensive traits against common predators, we compared bird predation pressures and the corresponding avoidance measures of cocoons of two nettle moth species, which utilize contrasting avoidance strategies: Parasa lepida (investing predominantly in primary defense) and Monema flavescens (investing predominantly in secondary defense). Field censuses revealed that bird predation was the most significant mortality factor for both species. The survival rate of cocoons was significantly higher for M. flavescens than for P. lepida, although M. flavescens were more conspicuous than P. lepida . Measurement of prepupae (cocoon content) mass, and experiments on the feeding preferences of the prepupae of both species using chicks, confirmed a similar quantity and quality of both speciesʼ prepupae as prey items. Our results were explained by the advantage of cocoon hardness outweighing the disadvantage of cocoon conspicuousness. The predation behavior of wild birds suggested that they spent considerably longer handling than searching for cocoons, which accounted for their cocoon preference for P. lepida over M. flavescens in the context of optimal foraging theory. Our results suggested that secondary defense was more effective in reducing bird predation than primary defense in limacodid cocoons. Abstract : We compared bird predation pressures and the corresponding avoidance measures of cocoons of two nettle moth species, which utilize contrasting avoidance strategies: Parasa lepida (investing predominantly in primary defense) and Monema flavescens (investing predominantly in secondary defense). Our results suggested that secondary defense was more effective in reducing bird predation than primary defense.